Ruskin After 200
XVI, 248 p. 34 illus.
Keywords: This edited volume offers new models for engaging with the work of John Ruskin, the Victorian art critic, architectural and educational theorist, amateur meteorologist and naturalist who gradually became an outspoken critic of capitalist economics and industrialization’s toll on the environment. Two hundred years after Ruskin’s birth, his relevance to art, literature, history, architecture, economics and natural science has not ebbed. However, the nature of Ruskin’s relevance has evolved considerably. This volume offers a cross-section of current scholarship, showing how a range of scholars continue to engage with Ruskin’s work in their research. The chapters provide a snapshot both of what scholars need from Ruskin now and how they continue to develop methodologies that allow them to keep in honest conversation with his writing – work that is wide-ranging, visionary and nuanced, but also elusive, promiscuously mixing the symbolic and scientific, and at times, deeply marred by the shortcomings of sexism, racism and rigid hierarchical thinking. Sara L. Maurer is Associate Professor Emerita of English at the University of Notre Dame, USA. Judith Stoddart is Vice Provost for University Arts and Collections and Associate Professor of English at Michigan State University, USA. Deanna K. Kreisel is Associate Professor of English and co-director of Environmental Studies at the University of Mississippi, USA. Amy Woodson-Boulton is Professor of History at Loyola Marymount University, USA.